POSITIONING MEETINGS, INCENTIVES, CONFERENCES AND EXHIBITIONS, AS A STRATEGY FOR PRODUCT DIVERSIFICATION IN BEACH HOTELS OF MOMBASA COUNTY, KENYA - NZIOKA, ALICE (Machakos University, 2019)
The study purposed to investigate Meetings, incentives, conventions and exhibitions, abbreviated “MICE” as an important element of tourism product innovation and diversification in Kenya. This paper had specific reference to the Beach Hotels in Mombasa County in the Kenyan Coast, which has traditionally offered vacation and leisure tourism product. As one of the major sectors within the global tourism industry, MICE have long been recognized as a sector that gives direct and indirect revenue for host destinations, creates employment opportunities and generates foreign exchange. As a consequence of all these major characteristics, the number of destinations vying for this industry is increasing (UNWTO, 2014). This study adopted a census approach while data collection took a two pronged approach. A validated questionnaire was administered to the respondents while a focus group discussion was held with selected hotel owners from the county. Results from this study indicate that during the period of focus 50% of the study hotels offered incentive tours while 33% offered exhibitions and trade fairs. The proportion of MICE earning compared to the total earning in the beach hotels grew from 21% in 2013 to 51% in 2017. The study found that 38% of the hotels are increasing their marketing targeting MICE, 31% are investing in developing their facilities. Seventy percent of the respondents said that the MICE product need diversification as an opportunity for growth as well as income to cushion the hotels during the seasonal fluctuations of the leisure tourism. Results showed that 60% of the hotels have not exploited their advantage of being on the beach to offer more incentive tours. The study recommends that beach hotels address new and existing innovations and technological solutions to diversify their businesses by offering products that incorporate business with leisure packages to be able to maximize on their revenue all year round
Keywords: MICE; Tourism product; Innovations; Destination; Diversification; Beach Hotel; Revenue